Semiotic Study: Analysis of Bullying in The Pyramid Game Television Series - Sidharta, Veranus; Anisti, Anisti; Imran, Maharani (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2025)
Bullying often occurs in the school environment, a place that should be a place for positive learning and character development for students. However, reality shows that schools can also be an arena for the reproduction of social violence, where hierarchy, power, and domination become an inseparable part of student interactions. One of the media that represents Bullying is the drama film Pyramid Game. This drama centers on the story of a new student at Baekyeon Girls' High School in Seoul who must face physical and mental violence after being selected as the lowest-ranking student in a popularity vote held at school. With the film's background, the study aims to analyze the representation of Bullying in the movie "Pyramid Game" using Roland Barthes' semiotic approach. The results of the study show, based on the analysis of Roland Barthes' semiotic theory, that Bullying in schools can not only be understood through the physical actions that occur (denotation) but also include deeper meanings related to power, domination, and social norms that are formed in the context of the interaction (connotation). Furthermore, the myths generated from this situation reinforce and justify violent behavior, making it appear as an integral part of school life.